(untitled) (Northern University Journal of Law, 2015)
Medical negligence is a clear violation of right to health by a professional group who are actually on duty to protect when emergency strikes and the health rights are under threat. Medical negligence is lately a popular topic of attention and discussion in many developed states and consequently many of them have enacted and established separate Acts and courts to strengthen health care laws. However in Bangladesh there is no specific and comprehensive legislation to prevent medical negligence though many legal provisions are there under different statutes which are not precisely codified. This article in this background has made an effort to define medical negligence, present laws concerning medical negligence of Bangladesh with their major loopholes and lastly recommends some actions to come on strong preventing such violation of health-care rights. Northern University Journal of Law Vol.IV 2013; p.67-81